Implementation of Supervision and Guidance of Notaries Who Do Not Carry Out Their Positions by the Regional Supervisory Council - Dewi Tjandraningsih; Felina (The International Journal of Law Review and State Administration, 2024)
The objectives of this research are 1. To examine the factors that prevent Notaries from carrying out their positions after being appointed and taking the oath. 2. To find out the implementation of supervision and guidance of Notaries by the Regional Supervisory Council. 3. To find out the legal consequences given by the Regional Supervisory Council. Research method. This research method uses a juridical legal approach to analyze regulations and legislation related to problems. Empirical to analyze law in society. Techniques for collecting data through Documentation Studies as legal research, which includes legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials. Conclusion The factors that cause Notaries to not carry out their positions after being appointed and sworn in are due to a lack of honesty and discipline of the Notary. Implementation of supervision and guidance to Notaries by the Tangerang City Regional Supervisory Council. At this time it has been done quite well and is optimal.The authority of the Regional Supervisory Council can carry out inspections, guidance, supervision, and summons to Notaries who commit violations